MRSA Patients Perception of Quality in the Healthcare Services of Private Hospitals in Raipur (International Journal of Food and Nutritional Sciences, 2022)
One of the main, fundamental ideas in service marketing is service quality. Hospital marketing is a significant industry where the goal of service quality is to satisfy patients' expectations for the quality of care fully they receive. The paper aims to investigate the Methicillin-resistant Staphylococcus aureus (MRSA) patients' perception with the care they received at the private hospitals in Raipur. This descriptive study of nature is important because it clarifies the nature of the current situation. Samples were collected using the stratified-random clustered sampling method. SPSS 20.0 and Microsoft excel version 13 is used to handle data and statistical analysis. Using Five-point Likert scale, a well-structured questionnaire, was used to get data from the respondents. The researcher used gap score analysis, and descriptive statistics in this investigation.